2015
DOI: 10.1111/ases.12213
|View full text |Cite
|
Sign up to set email alerts
|

Successful laparoscopic extirpation of a large omental lipoblastoma in a child

Abstract: Omental lipoblastoma is extremely rare among benign tumors. We herein report the case of a child who underwent laparoscopic extirpation of a large omental lipoblastoma. A 4-year-old girl was diagnosed with an intra-abdominal solid tumor. Abdominal imaging revealed a fat density mass that was well encapsulated and measured 18 × 15 × 7.5 cm in size. Considering the MRI findings and movability of the tumor, we strongly suspected that the lesion was an omental lipoblastoma. We initially decided to perform laparosc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…They concluded that for large abdominal tumors in children also, the laparoscopic approach could be recommended as the first procedure when the tumor is preoperatively considered to be benign and resectable. 7…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that for large abdominal tumors in children also, the laparoscopic approach could be recommended as the first procedure when the tumor is preoperatively considered to be benign and resectable. 7…”
Section: Discussionmentioning
confidence: 99%